2005
DOI: 10.1254/jphs.fp0050078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of [5-(2-Methoxy-5-fluorophenyl)furan-2-ylcarbonyl]guanidine (KR-32560), a Novel Sodium/Hydrogen Exchanger-1 Inhibitor, on Myocardial Infarct Size and Ventricular Arrhythmias in a Rat Model of Ischemia/Reperfusion Heart Injury

Abstract: Abstract. The cardioprotective effects of the novel sodium / hydrogen exchanger-1 (NHE-1) inhibitor KR-32560 {[5-(2-methoxy-5-fluorophenyl)furan-2-ylcarbonyl]guanidine} were studied in an anesthetized rat model of 30-min ischemia / 2.5-h reperfusion heart injury. KR-32560 (0.01 -1 µM) dose-dependently inhibited NHE-1-mediated rabbit platelet swelling induced by intracellular acidification. KR-32560 at 0.1 and 1.0 mg / kg (i.v. bolus, given 10 min before ischemia) reduced infarct size from 65.9% (control) to 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…During 30 min of ischemia, most VF occurred between 4 and 8 min. This arrhythmogenicity is similar to that reported by others using a similar rat model of ischemia / reperfusion with 30 min of ischemia (29). It is easily to understand that the ischemia-injured myocardium undergoes a period vulnerable to arrhythmogenic factors.…”
Section: Disscusionsupporting
confidence: 89%
“…During 30 min of ischemia, most VF occurred between 4 and 8 min. This arrhythmogenicity is similar to that reported by others using a similar rat model of ischemia / reperfusion with 30 min of ischemia (29). It is easily to understand that the ischemia-injured myocardium undergoes a period vulnerable to arrhythmogenic factors.…”
Section: Disscusionsupporting
confidence: 89%
“…), and the surgical procedure was performed as previously described (16,32). The trachea was intubated and connected to a rodent ventilator (SAR 830 / P ventilator; CWE, Inc., Ardmore, PA, USA) for artificial ventilation with room air (stroke volume, 10 ml / kg; 60 strokes / min) to keep blood gases (pCO 2 and pO 2 ) within normal ranges.…”
Section: Isolated Rat Heart Model Of Global Ischemia/reperfusioninducmentioning
confidence: 99%
“…1) is significantly more potent in inhibiting intracellular pH recovery in PS120/NHE-1 (h NHE-1 transfected) cells compared to cariporide (Lee et al, 2005c). We also reported that KR-32560 significantly reduces myocardial infarction as well as the incidence of various types of ventricular arrhythmias in an anesthetized rat model of I/R heart injury (Park et al, 2005). It also exerts an inhibitory effect on the aggregation of washed rabbit platelets induced by collagen and arachidonic acid .…”
Section: Introductionmentioning
confidence: 82%
“…It also exerts an inhibitory effect on the aggregation of washed rabbit platelets induced by collagen and arachidonic acid . KR-32560 appears to mediate its beneficial effects through NHE-1 inhibition, as evidenced by its reduction of Na + propionate-induced, NHE-1-mediated rabbit platelet swelling (Park et al, 2005). In the present study, we evaluated the cardioprotective effects of KR-32560 in globally ischemic isolated rat hearts with special emphasis on elucidating the involvement of prosurvival proteins (Akt, GSK-3β and eNOS) and antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%